2011
DOI: 10.3109/09637486.2011.582461
|View full text |Cite
|
Sign up to set email alerts
|

Blue-green algae (Arthrospira platensis) as an ingredient in pasta: free radical scavenging activity, sensory and cooking characteristics evaluation

Abstract: The effects of semolina enrichment with blue-green algae (Arthrospira platensis) at three different levels (1, 2 and 3 g/100 g of semolina) on the colour, cooking properties, firmness, free radical scavenging activity and sensory characteristics of pasta are reported. Microalgae addition resulted in higher swelling index and lower cooking loss than the control sample. A significant increase in pasta firmness was evidenced with an increase of added microalgae due to structural reinforcement. In addition to colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 5 publications
6
39
0
Order By: Relevance
“…Cooking increased the L value of pasta by an average of 3.0 ± 2.2, decreased the a value by an average of 3.4 ± 0.6, and decreased the b value by an average of 8.7 ± 2.0. The impact of cooking on pasta color could be attributed to the higher water content of cooked pasta and the degradation or leaching of color pigments in the cooking water (Zouari and others ; Jayasena and Nasar‐Abbas ).…”
Section: Impact Of Enrichment and Process Specifications On The Qualimentioning
confidence: 99%
See 2 more Smart Citations
“…Cooking increased the L value of pasta by an average of 3.0 ± 2.2, decreased the a value by an average of 3.4 ± 0.6, and decreased the b value by an average of 8.7 ± 2.0. The impact of cooking on pasta color could be attributed to the higher water content of cooked pasta and the degradation or leaching of color pigments in the cooking water (Zouari and others ; Jayasena and Nasar‐Abbas ).…”
Section: Impact Of Enrichment and Process Specifications On The Qualimentioning
confidence: 99%
“…The enrichment level of pasta showed a significant negative correlation to its overall quality (truer¯ = −0.70), appearance (truer¯ = −0.84), and flavor (truer¯ = −0.83), reflecting the lower acceptance of enriched pasta. Exceptions were pasta enriched with 15% unripe banana flour (Agama‐Acevedo and others ), 6% mushroom powder, 15% Bengal gram flour, 12% defatted soy flour (Kaur and others ), or 1% to 3% dried green‐blue microalgae (Zouari and others ). For these enrichment ingredients, the overall quality of the pasta increased slightly when compared to pasta with no enrichment (Table ).…”
Section: Impact Of Enrichment and Process Specifications On The Qualimentioning
confidence: 99%
See 1 more Smart Citation
“…Its reason could be due to higher content of phenol which is able to decrease DPPH free radicals by their hydrogen‐donating ability in the corn snacks. Zouari et al () reported that the use of 2 g blue‐green algae ( Arthrospira platensis )/100 g of semolina used for pasta development showed an increase in the free radical scavenging activity as compared with control samples. They also found that the antioxidant activity of the pasta enhanced the nutraceutical properties.…”
Section: Resultsmentioning
confidence: 99%
“…These dumplings are rich in carbohydrates but poor in protein content. Incorporation of legume flour (Petitot et al 2010;Shogren et al 2006;Zhao et al 2005) and algae (Fradique et al 2010;Zouari et al 2011) into pasta can increase protein content. In addition, incorporation of 50% soy flour into spaghetti increased the content of proteins and essential amino acids: lysine, threonine, methionine, isoleucine and leucine (Shogren et al 2006).…”
Section: Introductionmentioning
confidence: 99%